Projeto de sistema de controle embarcado para controle de voo de quadricópteros - Madruga, Sarah Pontes (2018)
In this project, we developed an embedded system for a ﬂight cotroller applied to quadrotor UAVs. Built with accessible components, open hardware architecture and open software, it makes possible the tests and implementation of new control algorithms by the user, setting it apart from the most common alternatives available on the market. Therefore, there is a sensoring system for capturing and recording the quadrotor odometry, the angular velocity com mandsaresentto the motors via PWM,and the processing is madeona Raspberry Pi3. For architecture validation, experiments were performed on each component, individually and together with the whole system, analysing then the aplicability to the desired goal. Furthermore, a study of the mathematical modeling and structure of a quadcopter was conducted. Lastly, the tuning of a Proportional Integral Derivative controller was tested to verify the operation of the developed device.